2020
DOI: 10.24310/ejfbejfb.v10i1.6688
|View full text |Cite
|
Sign up to set email alerts
|

How do family responsible ownership practices enhance social responsibility in small and medium family firms?

Abstract: This paper aims to measure the influence of the family responsible ownership practices on the socially responsible behaviour of family small and medium firms. To reach this purpose, we define six hypothesis and we apply an empirical testing of an integrative model. Based on a sample of 84 family SMEs, we use structural equation modelling to test for possible relationships within and between the constructs. This study reveals the relevance of the family responsible ownership practices as a driver that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Others (Gaglio, 2014) have suggested that professionalism may require proper development of situated skills developed during daily activities and actions. Scholars have linked professionalism to positive influences on performance and innovation (Diéguez-Soto et al , 2016), effective relationships with customers (Parry et al , 2011) and socially responsible management (Aragon-Amonarriz and Iturrioz-Landart, 2020). Attributes scholars (Cheng and Wong, 2015) associate with professionalism include passion, sensitivity and open-mindedness to new trends; team-oriented attitude; competence and skills; emotional self-control; professional ethics; leadership by example; and perfectionism.…”
Section: Resultsmentioning
confidence: 99%
“…Others (Gaglio, 2014) have suggested that professionalism may require proper development of situated skills developed during daily activities and actions. Scholars have linked professionalism to positive influences on performance and innovation (Diéguez-Soto et al , 2016), effective relationships with customers (Parry et al , 2011) and socially responsible management (Aragon-Amonarriz and Iturrioz-Landart, 2020). Attributes scholars (Cheng and Wong, 2015) associate with professionalism include passion, sensitivity and open-mindedness to new trends; team-oriented attitude; competence and skills; emotional self-control; professional ethics; leadership by example; and perfectionism.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the conclusion drawn by other scholars using samples from other countries. For Spanish family firms, family responsible ownership practices as a driver that influences corporate socially responsible practices [51], and family engagement can promote the corporate social responsibility to a certain extent [21]. Additionally, American family-controlled public-listed companies tend to adopt environment-friendly strategies more effectively and have a better environmental performance [18].…”
Section: Discussionmentioning
confidence: 99%